A comparative study on the tax and fee reduction policies for sustainable development: Empirical analysis from the world’s three major economies in tackling COVID-19 - Yujuan, Ma; Guangli, Yang; Bo, Li (Frontiers in Environmental Science, 2022)
The global COVID-19 epidemic in 2020 has caused a significant drop in many countries’ employment rates and economies. Numerous countries have implemented a number of tax and fee reduction policies in response to the COVID-19 epidemic. This essay analyzes the tax and fee policies and results of the three largest economies in the world—China, the United States, and Japan—in response to COVID-19 between 2020 and 2021. We will first compare the effects of tax and fee reduction policies horizontally across China, the US, and Japan. The second step is to compare the effects of tax and fee reduction policies. According to the study, China, the United States and Japan have each implemented separate tax and fee policies in response to COVID-19. The United States primarily provides corporate income tax, personal income tax relief, and increased social welfare and subsidies that reduce the tax burden of enterprises, stimulate the vitality of enterprises, increase the disposable income of residents, stimulate consumption, and thus promote economic growth; Japan primarily provides income tax, consumption tax and business tax relief to reduce the cost of consumption for residents, increase corporate profits and cash flow, restore economic growth and stabilize employment. China primarily provides tax relief for VAT, corporate income tax and social security funds. It indirectly lowers the selling price of products, reduces the operating costs of enterprises, increases personal disposable income, stimulates consumption, promotes the growth of business performance and plays a certain role in curbing inflation. Based on the empirical analysis of the impact of different tax and fee reduction policies on the economy and employment in China, the United States and Japan, it is of some relevance for other countries. Therefore, in response to COVID-19 or major emergencies, each country can formulate targeted tax and fee reduction measures based on its own national conditions to support economic growth and stable employment.